PENGARUH DISTRAKSI VIDEO FILM KARTUN TERHADAP KECEMASAN PADA ANAK DENGAN BRONKOPNEUMONIA YANG DILAKUKAN TERAPI INHALASI MENGGUNAKAN NEBULIZER - Riza Ayu Habiba; Komang Yogi Triana; Ni Made Dwi Ayu Martini (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Therapy in children with bronchopneumonia aims to provide a broncho-dilating effect or to widen the bronchial lumen. Children often exhibit uncooperative behavior when given inhalation therapy using a nebulizer. Giving distraction by watching cartoons can reduce anxiety because it focuses on pediatric patients with other things besides the feeling of discomfort they feel. The purpose of this study aimed at determining the distraction effect of Cartoon film video on anxiety in children with bronchopneumonia who experienced inhalation therapy using a nebulizer. The study design was pre-experimental, namely one group pre-test-post test design. The total samples were 30 people, using a purposive sampling technique. The data collection instrument used Child Anxiety Scales. Data were analyzed using a paired t-test. Anxiety before being implemented cartoon film video distraction was 70% in the medium anxious category and after being implemented cartoon film video distraction was 56.7% in the mild anxiety category. The results of the analysis obtained p = 0.000, which means that there is an effect of cartoon video distraction on anxiety in pediatric patients with bronchopneumonia who undergo inhalation therapy using a nebulizer. It is recommended that health service provide cartoon film video distraction to pediatric patients who are experienced inhalation therapy using a nebulizer.